Distribution of causes of acute abdominal pain in children that presented to a state hospital radiology unit according to age, gender and pathology origin - Tiryaki Baştuğ, Betül (The European Research Journal, 2019)
Objectives: The term “acute abdomen” refers to any sudden non-traumatic disorder whose chief manifestations are located within the abdominal area. In this condition, urgent operation may be necessary. The aim of this study was to investigate the distribution of causes of acute abdominal pain in children according to their age, gender and origin of pathology, who presented to a state hospital radiology unit in Turkey that had undergone standardised abdominal sonography and computed tomography imaging if necessary.Methods: This study was designed as a retrospective investigation. A sample of 1000 patients (568 males and 432 females) were selected from a pool of 3452 paediatric patients between 2014 and 2016.Results: Acute abdomen in the paediatric age group occurred more frequently in males than females. The most common age of presentation with acute abdominal pain was between 7 and 15 years. The most common medical cause was mesenteric lymphadenitis (11%). In females, mesenteric lymphadenitis, acute appendicitis and ovarian cyst rupture were the predominant causes, whereas mesenteric lymphadenitis, acute appendicitis and urinary system pathologies were predominant in males. Conclusions: When evaluating a child with acute abdominal pain, the most important components include taking a thorough patient history and performing repeated physical examinations. Selective use of appropriate laboratory and radiological investigations may be necessary in order to establish a specific diagnosis.